Two interesting cases of left atrial myxoma - Alurkar, VM; Neupane, S (Kathmandu University Medical Journal, 2010)
Atrial myxoma is the most common type of benign primary heart tumours. Most of these tumours are sporadic in origin occurring at 3rd to 6th decade of life, while hereditary forms do exist. They are mostly found in the left atrium followed by right atrium and ventricles. A left atrial myxoma may present with features of mitral valve obstruction, embolic phenomenon or systemic disease. On diagnosis, prompt surgical removal is necessary which usually gives a complete cure, though recurrences have been reported. We hereby present two cases of solitary left atrial myxoma. Key words: atrial myxoma; echocardiography; tumour impaction DOI: 10.3126/kumj.v8i1.3226 Kathmandu University Medical Journal (2010), Vol. 8, No. 1, Issue 29, 80-92